Generation of novel human MHC class II mutant B-cell lines by integrating YAC DNA into a cell line homozygously deleted for the MHC class II region. - Fabb, SA; Davies, A; Correa, I; Kelly, A; Mackie, C; Trowsdale, J; Ragoussis, I (1997)
The human B lymphoblastoid cell line (LCL) 721.174 sustains a large homozygous deletion in the major histocompatibility complex (MHC) class II region that results in an absence of DQ and DR molecules as well as a deficiency in the assembly and transport of class I molecules to the cell surface. The deleted genes include the transporters associated with antigen processing TAP1 and TAP2, DMA and DMB which are involved in editing class II bound peptides, and four genes whose roles in antigen processing are unclear; the low mass polypeptide genes LMP2 and LMP7, and DNA and DOB. To study this region we have integrated into 721.174 two overlapping yeast artificial chromosome (YAC) clones which cover the interval LMP2-DRA inclusive. Three clones (11.2A1.1, 4D1D10.1 and 4D1D10.2), containing complete copies of the transfected YAC, produced varying levels of mRNA from the LMP, TAP, DQ and DR genes and corresponding levels of LMP and TAP protein. Class I cell surface expression was restored in 11.2A1.1 and 4D1D10.1, as was DR expression in both 4D1D10 transfectants. These studies demonstrate the feasibility of introducing large groups of functional genes back into human lymphoblastoid cells sustaining deletions, with full restoration of biological function. The procedure could be exploited in order to restore all but one gene covered by the deletion, effectively producing a single gene defect. This could be used to introduce copies of genes engineered to contain mutations and to study cis regulatory elements at some distance from the chosen loci.